(untitled) (International Journal of Engineering and Computer Science, 2016)
A MANET is a type of ad-hoc network that consists of wireless mobile nodes communicates with each other without using wires, a fixed infrastructure, central administration and which establishes route from source to destination. In Mobile Ad-hoc Network (MANET), each node can freely move in any direction and every node also act as router as they forward traffic for other nodes. So, various routing protocols such as AODV, DSR, DSDV and OLSR are designed for routing in ad-hoc networks. This paper analyzed the literature of routing protocols which are discussed by comparing the various routing protocols on the basis of different schemes.